2022
DOI: 10.1088/1361-6501/ac8ca4
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to COVID-19 detection from x-ray images using angle transformation with GoogleNet and LSTM

Abstract: Declared a pandemic disease, COVID-19 has affected the lives of millions of people and had significant effects on public health. Despite the development of effective vaccines against the COVID-19 virus, COVID-19 case rates continue to increase worldwide. According to studies in the literature, artificial intelligence methods are used effectively for the detection of the COVID-19. Especially deep learning-based approaches have achieved very successful results in clinical diagnostic studies and other fields. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Numerous recent studies have also shown the superior role of superficial and deep learning-based intelligence in the diagnosis of COVID-19 patients using X-rays and CT scans with higher accuracy than the standard diagnostic approach [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous recent studies have also shown the superior role of superficial and deep learning-based intelligence in the diagnosis of COVID-19 patients using X-rays and CT scans with higher accuracy than the standard diagnostic approach [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haritha et al [ 190 ] used GoogleNet to classify X-ray images and predict COVID-19. Kaya et al [ 191 ] first applied the angle transformation (AT) on X-ray images. Then these images are trained using GoogleNet combined with LSTM.…”
Section: Application Analysis and Discussionmentioning
confidence: 99%
“…Deep learning, which can learn features directly from an original data, has achieved remarkable results in defect detection for industrial products [25,26], equipment fault diagnosis [27], and x-ray images-based COVID-19 detection [28]. Aslam et al [1] suggested that deep learning architectures can serve as a source of guidelines for designing and developing new solutions for leather defect inspection.…”
Section: Related Workmentioning
confidence: 99%